Experiences of priorities of investment for science and technology development at local level by advancing countries in the region - Lam Giang, Luu Thi; Dung, Bui Tien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Priorities of investment for science and technology (S&T) development at local level by other countries in the region are studied on basis of analysis of some components including friendly investment environment, policy environment and shifts of local economic structure. At the same time, the authors conducted studies of lessons by countries in the region to highlight priority policies for local S&T development in short-term, mid-term and longterm visions. Code: 15122901<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">